Design and Feasibility Analysis of an integrated Zero-Waste Palm Oil biorefinery for Sustainable Aviation Fuel Production and Greenhouse Gas Mitigation - Ijop, Admin; Fitriyah, Aidatul (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2025)
This study aims to design and assess the technical, environmental, and economic feasibility of an integrated Zero-Waste Palm Oil biorefinery for the production of Sustainable Aviation Fuel (SAF) and other value-added co-products. A quantitative-descriptive approach was employed, integrating process simulation using Aspen Plus V14, Life Cycle Assessment (LCA), and financial modeling to evaluate the system’s performance and sustainability. Primary data were obtained from operational palm oil mills. In contrast, secondary data were sourced from the International Energy Agency (IEA), the International Renewable Energy Agency (IRENA), Statistics Indonesia (BPS), and the Ministry of Energy and Mineral Resources (ESDM) during 2023–2024. The results demonstrate that the integrated biorefinery configuration, which combines thermochemical conversion pathways (pyrolysis, gasification, and Fischer–Tropsch synthesis) with biochemical processes (anaerobic digestion), achieves a mass conversion efficiency of 58.4 percent, net energy efficiency of 72 percent, and an Energy Return on Investment (EROI) of 4.97, exceeding the global bioenergy feasibility threshold of three. The LCA results indicate total Life-cycle emissions of 17.3 g CO?-eq per MJ, representing an 80.6 percent reduction relative to fossil-based Jet A-1 fuel, thereby meeting both CORSIA and RED II sustainability standards. The system also achieves a 95 percent reduction in solid residues, effectively realizing a near-zero-waste operation. Financial modeling reveals a net present value (NPV) of USD 68.2 million, an internal rate of return (IRR) of 17.6 percent, and a payback period of 6.2 years, confirming the project’s economic viability. Overall, this model establishes a scalable pathway for decarbonizing the palm oil industry through circular bioeconomy principles and positions Indonesia as a potential global hub for SAF production aligned with international carbon reduction targets.